Health promotion at local level: a case study of content, organization and development in four Swedish municipalities - Jansson Elisabeth VG; Tillgren Per E (BMC, 2010)
Abstract Background Several health determinants are related to local conditions and prerequisites at community level. For this reason, strengthening community action has been one of five strategies implemented in health promotion since the end of the 1980s. Such action includes setting priorities, making decisions, planning strategies, and implementing them to achieve better health. The aim of this paper is to obtain a deeper understanding of content, organization and processes in the development of local health promotion. Methods A qualitative multiple case study of four Swedish municipalities. The cases were analyzed in accordance with the principles of cross-case study analysis, and a content analysis of documents and interviews was conducted in two steps. First, a manifest content analysis was performed to identify present and former actors and measures. Thereafter, a latent content analysis was performed to investigate structures and processes in local contexts. Results The results of the inductive content analysis showed development of local health promotion in three phases: initiation, action, and achievement. Strengthening factors were local actors, health statistics and events. Hindering factors were lack of resources and vague objectives. External factors, e.g. national policies, were not perceived as prominent influencing factors. Media reports were regarded as having had an influence, but only to some extent. The content of local health promotion has developed from ad-hoc lifestyle and behaviour-related actions into structural, intersectoral actions related to determinants of health. Conclusions The municipalities have organized and developed their health promotion targets, actions and priorities on the basis of local needs and prerequisites. The three phases in the identified health promotion processes were experienced and documented as being subject to greater influence from internal rather than external strengthening and hindering factors in their local contexts.